2022
DOI: 10.18502/tim.v7i4.11494
|View full text |Cite
|
Sign up to set email alerts
|

The I-CAM-IR: Persian Translation, Cross-Cultural Adaptation and Revised Version of the I-CAM-Q

Abstract: Complementary and alternative medicine (CAM) has shown increasing acceptance, popularity, and use all around the world. The International Complementary and Alternative Medicine Questionnaire (I-CAM-Q) was developed to be a standard research instrument for achieving more reliable data and enabling researchers for comparing multiple studies on CAM use. This study aimed to provide a Persian translation of I-CAM-Q that also was adapted according to Iranian culture. The I-CAM-Q was translated and back-translated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…One limitation of this study was the lack of information on the exact duration and goals of CAM use in the included studies. Therefore, standard questionnaires with clear definitions of CAM use should be developed and utilized in future studies to enable meta-analysis and facilitate decision-making ( Chijan et al, 2022 ). Additionally, the high heterogeneity among the studies made it impossible to perform a meta -analysis.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this study was the lack of information on the exact duration and goals of CAM use in the included studies. Therefore, standard questionnaires with clear definitions of CAM use should be developed and utilized in future studies to enable meta-analysis and facilitate decision-making ( Chijan et al, 2022 ). Additionally, the high heterogeneity among the studies made it impossible to perform a meta -analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 36.0% of patients with chronic disease in Thailand indicated that they had used herbal medicine within the past 12 months [ 35 ]. Treatment with herbs was the preferred type of complementary and alternative medicine in patients living with human immunodeficiency virus [ 36 ] and hypertension [ 37 ]. Also, 42% of physicians in Italy believed that complementary and alternative medicine could play an integrative role in conventional medicine [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional descriptive-analytical study utilized the I-CAM-IR questionnaire (Supplementary file 1), which is the standard Persian version of the I-CAM-Q, an internationally recognized questionnaire on the use of CAM [ 1 , 22 ]. The I-CAM-Q is a self-administered questionnaire comprising four main sections designed to evaluate individuals' utilization of CAM.…”
Section: Methodsmentioning
confidence: 99%